Kondisi Siswa SMA Negeri 6 Palu dalam Pembelajaran Sejarah di Tengah Wabah Covid-19 - Charles Kapile (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2020)
This study aims to find out the form of adaptation of history learning process conducted by students during the Covid-19 pandemic and the obstacles faced during the learning process. This type of research is quantitative. Research data sources are informants, places/events, and documents. Questionnaire data collection techniques. The data analysis uses descriptive statistical analysis. Drawing conclusions using reason analysis derived from the study of the theory and the results of the discussion. This research produces data that in the midst of historical learning conditions in the midst of the Covid-19 outbreak Online or online learning allows students and teachers not to face-to-face but can take advantage of special online applications for learning, most choose to use home learning applications by 3.63%%. The obstacles faced when doing online learning are the lack of concentration of students when receiving materials because the situation is less conducive by 70.20%, no companion during learning by 64.8%, and limited digital media at home to support the online learning process by 0.25%.